2013
DOI: 10.1108/jieb-03-2013-0010
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative identification of learning effectiveness indicators among mainland Chinese students in culturally dislocated study environments

Abstract: Purpose -This exploratory research project investigated how mainland Chinese business students studying overseas conceptualize and describe the learning effectiveness of ten different instructional techniques commonly encountered in their business courses. A large numbers of mainland Chinese students enroll in business courses in private international institutions in Singapore -dislocated from their home cultures -but needing to adapt to Western learning curricula and ultimately to acquire proficiency in Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…A significant research implication of this study's findings lies in its support of other similar studies regarding the meshing hypothesis all of which suggest that faculty are 155 Teachinglearning style mesh hypothesis likely to reach only a selected few students if it is assumed that all students learn in the same way. The results of this study also support Rajaram and Collins' (2013) suggestion that culture alone may not dictate a student's preferred learning style and thus preferred teaching style. This is evidenced by the study's support of the mesh hypothesis which would not have been supported if there were a "culture alone" effect.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A significant research implication of this study's findings lies in its support of other similar studies regarding the meshing hypothesis all of which suggest that faculty are 155 Teachinglearning style mesh hypothesis likely to reach only a selected few students if it is assumed that all students learn in the same way. The results of this study also support Rajaram and Collins' (2013) suggestion that culture alone may not dictate a student's preferred learning style and thus preferred teaching style. This is evidenced by the study's support of the mesh hypothesis which would not have been supported if there were a "culture alone" effect.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies have reported that transnational MBA programs have exhibited a lack of appreciation of culture and diversity and fail to adjust their teaching approaches to different learning styles (Bolton and Nie, 2010;Pimpa, 2009). This has prompted a recent research stream which has investigated both intercultural and pedagogical issues that may impact foreign student satisfaction and learning outcomes (Burdett, 2014;Crossman and Bordia, 2008;Rajaram and Bordia, 2011;Rajaram and Collins, 2013). This research stream suggests that instructional delivery should be guided by intercultural awareness to assure appropriate teaching style -learning style fit.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research suggests that there are important differences between international and domestic students and that such differences may influence their service quality perceptions (Lillyman and Bennett, 2014;Moore and Bowden-Everson, 2012;Rajaram, and Collins, 2013;Andrade, 2006;Niles, 1995), and there is a need for further exploring the experiences of the international students (Bordia et al, 2013). Understanding differences between international and domestic students with regards to their service quality perceptions is increasingly important, as the number of people studying outside their country of citizenship has doubled during the period from 2000 to 2010 (AEI, 2013), and currently, more than 4 million international students are enrolled in tertiary education (OECD, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of learning, in our context, perceived learning effectiveness, is influenced by the learning circumstances, for example learning environment (Dunlosky et al, 2013 ), the approach of how the instructional techniques are effectively adopted and used based on the profile, and characteristics of the learners (Rajaram, 2020 ). A balanced approach and compatibility are required between the learning styles of students and correct mix of instructional delivery approaches for effective learning to occur (Rajaram & Collins, 2013 ).…”
Section: Resultsmentioning
confidence: 99%